Dao-Chi Powder Ameliorates Pancreatitis-Induced Intestinal and Cardiac Injuries via Regulating the Nrf2-HO-1-HMGB1 Signaling Pathway in Rats - Yao, Jiaqi; Miao, Yifan; Zhang, Yumei; Zhu, Lv; Chen, Huan; Wu, Xiajia; Yang, Yue; Dai, Xiaoyu; Hu, Qian; Wan, Meihua; Tang, Wenfu (Frontiers in Pharmacology, 2022)
Dao-Chi powder (DCP) has been widely used in the treatment of inflammatory diseases in clinical practice of Traditional Chinese Medicine, but has no trace in acute pancreatitis (AP). The purpose of this study is to evaluate the effect of DCP on severe AP (SAP) and SAP-associated intestinal and cardiac injuries. To this end, an animal model of SAP was established by retrograde injection of 3.5% taurocholic acid sodium salt into the biliopancreatic duct of rats. DCP (9.6 g/kg.BW) was administered intragastrically 12 h after the modeling. Pancreases, duodenum, colon, heart, and blood samples were harvested at 36 h after the operation for the histological and biochemical detections. On this basis, another part of the experiment was designed to determine and compare the tissues distributions of DCP components in Sham group and SAP group. Moreover, molecular docking analysis was employed to investigate the interactions between the potential active components of DCP and targets (Nrf2, HO-1 and HMGB1). Consequently, DCP treatment decreased serum levels of amylase and the markers of gastrointestinal and cardiac injury, further alleviated the pathological damage in pancreas, duodenum, colon, and heart of SAP rats. Mechanistically, DCP rebalanced the pro-/anti-inflammatory cytokines, inhibited MPO activity and MDA levels within these tissues. Furthermore, Western blot and PCR results showed that DCP intervention enhanced the expression of Nrf2 and HO-1 in duodenum and colon of SAP rats, while inhibited the expression of HMGB1 in duodenum and heart. HPLC-MS/MS uncovered that SAP promoted the distribution of ajugol and oleanolic acid to duodenum, whereas inhibit the distribution of liquiritigenin to heart and ajugol to colon. In addition, molecular docking analysis confirmed that the six screened components of DCP had relatively good binding afﬁnity with Nrf2, HO-1 and HMGB1. Among which, oleanolic acid had the highest affinity with HO-1. Altogether, DCP could alleviated SAP-induced intestinal and cardiac injuries via inhibiting the inﬂammatory responses and oxidative stress partially through regulating the Nrf2/HO-1/HMGB1 signal pathways, providing additional supportive evidence for the clinical treatment of SAP.